AB1428-HPR Fatigue in patients with quiescent systemic lupus erythematosus: The role of dehydroepiandrosterone sulfate. (23rd January 2014) - Overman, C.L.; Hartkamp, A.; Bossema, E.R.; Bijl, M.; Godaert, G.L.R.; Bijlsma, J.W.J.; Derksen, R.H.W.; Geenen, R.
Abstract : Background: Fatigue is a major problem in systemic lupus erythematosus (SLE). In some patient groups, associations between fatigue and low levels of dehydroepiandrosterone (DHEA) and its sulfate (DHEAS) have been found. Low levels of DHEA(S) may also play a role in SLE fatigue. Objectives: To compare 1) serum DHEAS levels and fatigue between female patients with quiescent SLE and healthy women, and 2) fatigue between SLE patients with low and normal DHEAS levels. Methods: Included were 60 female patients with quiescent SLE (31 using prednisone and 29 not using prednisone) and 60 age-matched healthy women. Serum DHEAS levels were determined using an Advantage Chemiluminescense System. Fatigue was measured with the Multidimensional Fatigue Inventory (MFI). Groups were compared on DHEAS and fatigue using Chi 2 and Mann-Whitney U tests. Results: Compared to healthy women, SLE patients were more fatigued ( p ≤0.001) and more often had DHEAS levels below the lower limit of normal ( p <0.001), in particular those using prednisone. Compared to SLE patients with normal DHEAS levels, patients not using prednisone reported less fatigue on four out of five fatigue dimensions ( p ≤0.03). SLE patients using prednisone with low and normal DHEAS levels reported a similar level of fatigue ( p ≥0.39). Conclusions: Although in patients with quiescent SLE low serum DHEAS levels are more frequent and fatigue levels are higher than in healthy people, low DHEAS levels are not - or even inversely - related to fatigue. After our previous finding that DHEA administration does not reduce fatigue, this result further indicates that low DHEA(S) levels alone do not offer an explanation for SLE fatigue. Disclosure of Interest: None Declared